IMUNOKIMIAWI PGE2 USUS ILEUM YANG KEKURANGAN ENERGI PROTEIN - R. Heru Prasetyo (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2011)
Diarrhoeal disease mortality which suffered by children less than five years due to protein energy deficiency is increased significantly.The pathological mechanisms are not known in detail yet. The objective of this research was able to explain the intestine motility inprotein energy deficiency of mice Balb/c. Hormonal mechanism that regulates the intestine motility is roled by prostaglandine E2 hormone(PGE2). The observed variable was the immunity component of PGE2. The measurement was performed using immunohistochemistrymethod with monoclonal antibody against PGE2 to the ileum mice tissue. The result of this study showed that protein energy deficiencymice had much reduced PGE2 (reduction from 1492 to 145, p = 0.000 ). In conclusion, the marked decrease of ileum PGE2 will decreaseintestine motility and it may be one cause of the high diarrhoeal mortality due to protein energy deficiency.